Day of Fire: An Oral History Perspective on the Bush White House on 9/11. Issue 3 (9th December 2021) - Nelson, Michael
Abstract: Presidential crises come in multiple forms. The September 11, 2001 terrorist attacks on New York and Washington DC exemplify a type of crisis marked by a combination of four qualities: (1) a sudden event that is (2) unanticipated and (3) requires (4) an urgent response by the president. This article offers an account of the day's unfolding events as White House and other officials experienced them. It does so in the words of participants, most of them drawn from lengthy and recently-released interviews conducted by the University of Virginia's Miller Center as part of its George W. Bush Oral History. Like all historical methods, oral history is imperfect. Among its advantages, however, is that it supplements documentary White House records that have become steadily less revealing. The article concludes with a brief discussion of certain post-9/11 measures designed to enhance security, some of which have been effective but none of which forestalled the January 6, 2021 assault on the Capitol.